Fishery Development and Exploitation in South East Australia - Novaglio, Camilla; Smith, Anthony D. M.; Frusher, Stewart; Ferretti, Francesco; Klaer, Neil; Fulton, Elizabeth A. (Frontiers in Marine Science, 2018)
Understanding the full extent of past ecological changes in human-influenced marine systems is needed to inform present management policies, but is often hampered by the scarcity of information about exploitation practices and population status over the entire history of fishing. The history of commercial fishing in South East Australia is relatively recent and thus easier to document. Our aim is to reconstruct such history and to use this information to understand general patterns and consequences of fishing exploitation. Intense exploitation of marine resources arrived in South East Australia with European colonization in the early 1800s, and unregulated sealing, whaling and oyster dredging resulted in the first documented significant impact on local marine populations. Exploitation extended to demersal resources in 1915 when the trawl fishery developed. Between the early 1800s and the 1980s, some of the exploited stocks collapsed, but fishing moved further offshore and in deeper waters as technology improved and new resources became available or were discovered. This phase of fisheries expansion masked the unsustainable nature of some fishing industries, such as trawling and whaling, and postponed the need for management regulations. From the 1990s onward, an increasing awareness of the depleted nature of some fisheries led to the establishment of management strategies aiming at a more sustainable exploitation of target stocks and, from the mid-2000s onwards, management strategies were revised and improved to better address the effect of fishing on multiple components of marine ecosystems. This led to the recovery of some depleted populations and to increased habitat protection. The relatively short history of fishing exploitation and the small scale of the fishing industry in South East Australia played a significant role in limiting the magnitude of fishing impacts on local populations and helped to achieve recoveries when fisheries restrictions were imposed. However, the experience in South East Australia also shows that ecological improvements for some depleted populations can be slow, suggesting that the time to recovery may be longer than expected despite relatively low historical and present levels of exploitation, favorable social conditions and a large investment in resource management and scientific research.